PENGARUH PENGGUNAAN TIPE PEMBELAJARAN EXAMPLE NON EXAMPLE TERHADAP PENGUASAAN MATERI - Harum Diana; Arwin Achmad; Berti Yolida (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
The purpose of this research was to measure the influence of using Example Non Example learning type toward mastering of characteristics of living subject by students Class VII SMP NEGERI 3 Gadingrejo Academic Year 2011/2012, the average of mastering of characteristics of living subject in the classroom that using Example Non Example learning type higher than class discussion methods. Design used in this research was pretest-posttest design of non-equivalent groups. The sample was 31 students VIIA as control class and 31 students VIIF as experiment class. The research data were taken with the pretest and posttest. Data analysis was performed by t test. The results showed that the class that using Example Non Example learning type influenced significant in mastering of characteristics of living subject, consist of breathing, moving, sensitive to stimuli, eat, excrete the rest, grow and reproduce and adapt. Additionally average subject matter characteristics of living things on the students class that using Example Non Example learning type higher than students that using learning discussions. Keywords: Characteristics of Living Subject, Example Non Example, Mastery of Content.